Every day is Earth Day - O'Connor, Jane.; Ivanov, A. (Aleksey); Ivanov, O. (Olga) (New York : Harper, 2010)
When Nancy, the girl who loves to use fancy words, learns about Earth Day and "being green," her enthusiasm causes problems at home.
Keywords: Earth Day -- Fiction; Environmental protection -- Fiction; Family life -- Fiction; School stories; Vocabulary -- Fiction